Penerapan Metode Ahp untuk Subsistem Pendukung Pemilihan Supplier pada Outhouse Costing Integrated System (Ocis) di Pt Adm - Surjandy, Surja; Melva, Melva (Bina Nusantara University, 2014)
In general automotive development, especially car, PT Astra Daihatsu Motor (ADM) continuously improves quality and service to supply vehicles in Indonesia. To support the improvement of quality and service, PT ADM continues to improve technology-based system to assist in providing vehicle parts of production process requirements. Therefore Purchasing division is very important in this process. Besides, supplier is a very important role in making and supplying parts for the company. PT ADM has a new system used to improve bidding process. Based on the discussion, price was not the only thing significant. There were other things to consider, especially in selecting the right supplier. Realizing the system does not cover all areas, therefore, it needs Decision Support System with AHP method to filter suppliers. So that, the company will automatically have good supplier. At least, the supplier meets company standard, especially purchasing department. This research concludes that using AHP Method is very effective for filtering supplier so that the company can make sure that only capable supplier or supplier which meets company standard may join the tender to supply the goods or parts. This paper combined AHP Methodology as the first selection using pairwise scoring and Analysis Sensitivity Methodology used to take decision which supplier is in line with project requirements.